Deflection and Elastic Modulus Assessment of Subgrade in Flexible Pavement mixed with Waste Tire Scrap Material - Sarkar, Sujoy; Biswas, Sumit Kumar; Chakraborty, Saibal (Engineering, Technology & Applied Science Research, 2024)
This study aims to assess the deflection and elastic modulus (Es) of subgrade in flexible pavements, focusing on a comparative analysis between pavements with clayey soil subgrade and subgrade modified with tire scrap. The research utilized Falling Weight Deflectometer (FWD) for measuring subgrade deflection, essential in evaluating pavement performance. The FWD applied a dynamic load to the pavement, with deflection measurements processed using the KGP-BACK software to calculate the Es of the pavement subgrade. This approach included assessing the Lower Layer Index (LLI) and Es of the subgrade. Findings revealed a notable reduction of 37.5% in deflection and 2.68 times increase in Es for the tire scrap modified subgrade pavement compared to the standard clayey soil subgrade pavement. These results demonstrate significant enhancements in pavement structure, underlining the potential of recycled materials in sustainable civil engineering practices.